Perbanyakan Mikoriza Indigenus Taman Nasional Gunung Ciremai dengan Berbagai Tanaman Inang - Ai Nurlaila; Ika Karyaningsih; Dede Kosasih; Ilham Adhya; Meindhika Giwantara; Wiwit Walinda (Institut Pertanian Bogor, 2024)
This study aimed to determine the effectiveness of the use of host plants in an effort to multiply mycorrhizal propagules indigenous to Gunung Ciremai National Park. The experimental method used a factorial complete randomized design with 2 factors. The first factor was the location of the source of inoculum by 3 levels: mixed forests, shrubs, and pine stands. The second factor was 4 types of host plant many as 4 levels: corn (Zea mays), sorghum (Sorghum bicolor. (L.) Moench), centro beans (Centrosema pubescens), and ruji beans (Pueraria javanica). Each treatment was repeated five times, so there were 60 experimental units. The spores were isolated by wet filtration and decantation methods adapted from Gerdemann and Nicolson (1963), followed by the modified sugar centrifugation method from Jenkins (1964). The observed parameter was the number of mycorrhizal spores. The data obtained were analyzed by a variance test (F test). To evaluate the treatment's effect and compare the selected treatments, Duncan's follow-up test was used at the level of 5%. The combination of the location of the shrub inoculum and the centro bean host plant showed the largest spore population, which was 222.60 per 50 g soil sample. Trapping techniques using host plants of corn, sorghum, centro beans, and ruji beans showed suboptimal results. The most common genera were Glomus (80%; 4 species), Gigaspora (10%, 1 species), and Acaulospora (10%, 1 species). Glomus was evenly found in all trapping results. Keywords: Acaulospora, Glomus, mycorrhiza, propagules, spores